Ecological carrying capacity of alpine grassland in the Qinghai-Tibet Plateau based on the structural dynamics method - Fang, Yi-ping; Zhu, Fu-biao; Yi, Shu-hua; Qiu, Xiao-ping; Ding, Yong-jiang (Environment, Development and Sustainability, 2021)
The ecological carrying capacity (ECC) is a barometer for ecosystem sustainability. Alpine grassland ecosystems are thought to be the most sensitive ecosystems to climate change. Yet, the ECC of alpine grassland is less well understood. This study aims to establish a structural dynamics model that it enables us to capture different states, changes in tendency, as well as major driving variables of alpine grassland ECC. The results showed that the active layer thickness had a significant adverse effect on ECC (p = 0.05), while precipitation, air temperature, net primary productivity (NPP) had a significant positive effect on ECC (p = 0.01). And anthropogenic factors like fenced pasture, warm shed area, sown grassland area, and livestock density also caused an increase in ECC (p = 0.05). The ECC of alpine grassland displayed an increasing trend on the Qinghai-Tibetan Plateau (QTP). The mean contributions of active layer thickness, NPP, precipitation, and air temperature to the ECC were - 10.0% (p = 0.05), 52.1% (p = 0.01), 17.0% (p = 0.01), and 12.0% (p = 0.01), respectively. From 1980 through 2013, the average annual growth of ECC was 9.1%. The sensitivity of the grassland ECC to major climate variables fluctuated, with periods of high and low sensitivity recorded. On a geographical scale, the Tibet Autonomous Region had higher levels of sensitivity to change, with larger fluctuations, in comparison with Qinghai Province. These findings could provide an important basis for effective adaptation of alpine ecosystem to climate change.